Predictive factors of early recurrence after R0 resection of hilar cholangiocarcinoma: A single institution experience in China. (13th March 2019) - Hu, Hai‐Jie; Jin, Yan‐Wen; Shrestha, Anuj; Ma, Wen‐Jie; Wang, Jun‐Ke; Liu, Fei; Zhu, Ya‐Yun; Zhou, Rong‐Xing; Regmi, Parbatraj; Cheng, Nan‐Sheng; Li, Fu‐Yu
Abstract: Prediction of early postoperative recurrence is of great significance for follow‐up treatment. However, there are few studies available that focus on high‐risk factors of early postoperative recurrence or even the definition the exact time of early recurrence for hilar cholangiocarcinoma. Thus, we aimed to examine the optimal cut‐off value for defining the early in patients with R0 resection of hilar cholangiocarcinoma and to investigate prognostic factors associated with early recurrence. Two hundred and fifty‐eight patients with R0 resection of hilar cholangiocarcinoma between 2000 and 2015 were included. The minimum P value approach was used to define the optimal cut‐off of early recurrence. The prognostic factors associated with early recurrence were investigated. The optimal cut‐off value for dividing patients into early and non‐early recurrence groups after R0 resection of hilar cholangiocarcinoma was 12 months. Sixty‐two patients were recorded as early recurrence, and the remaining 196 patients were labeled as non‐early recurrence. Multivariate logistic regression analysis indicated lymph node metastasis (OR = 2.756, 95% CI 1.409‐5.393; P  = 0.003), poor differentiation (OR = 1.653; 95% CI 1.040‐2.632; P  = 0.034), increased postoperative CA 19‐9 levels (OR = 1.965, 95% CI 1.282‐3.013; P  = 0.002), neutrophil‐to‐lymphocyte ratio > 3.41 (OR = 5.125, 95% CI 2.419‐10.857; P  < 0.001) and age > 60 years (OR = 2.018, 95% CI 1.032‐3.947; P  = 0.040) were independent determinants of early and non‐early recurrence. Poor differentiation (HR = 2.609, 95% CI 1.600‐4.252; P  < 0.001), Bismuth classification type III/IV (HR = 2.510, 95% CI 1.298‐4.852; P  = 0.006) and perineural invasion (HR=2.380, 95% CI 1.271‐4.457; P  = 0.007) were independent factors of overall survival in the subgroup of patients who developed early recurrence. The optimal cut‐off value for dividing early recurrence after R0 resection of hilar cholangiocarcinoma was 12 months. Tumor differentiation, Bismuth classification, and perineural invasion were independent factors of overall survival in the subgroup of patients with early recurrence. Patients with risk factors should be monitored closely after curative surgery. Abstract : The optimal cut‐off value for dividing early and non‐early recurrence after R0 resection of hilar cholangiocarcinoma was 12 months. Tumor differentiation, Bismuth classification, and perineural invasion were independent factors of overall survival in subgroup of patients with early recurrence. Patients with risky factors should be monitored closely even after curative surgery.